Macroeconomics - Hall, Robert E.; Taylor, John B. (New York: W.W. Norton, 1997)
This textbook adopts a single-model framework to explain macroeconomic concepts, emphasizing the dynamic interactions between key economic variables. It integrates theoretical models with empirical data to illustrate how macroeconomic policies affect real-world economies.
Includes bibliography and index
Keywords: Macroeconomics